Effects of amino acids methionine, lysine, and taurine on feed intake and mRNA expression of appetite-related neuropeptides in layer-type chicks - Elham Ghashghaei; Minghui Wang; Ahmed Mijiyawa; Hai Lin (Poultry Science, 2025)
Amino acids in the brain modulate eating behavior and energy balance. The aim of the present study was to investigate the effects of DL-methionine (DL-Met), l-lysine monohydrochloride (L-Lys-HCl), and taurine (Tau) on feed intake and the mRNA expression levels of appetite-related hypothalamic neuropeptides in chicks. DL-Met, l-Lys-HCl, or Tau was intracerebroventricularly (ICV) administered to 5-day-old layer-type chicks, and the feed intake was recorded until 1 h post-injection. Quantitative PCR was performed to determine the hypothalamic mRNA expression levels of neuropeptide Y (NPY) and its receptors, agouti-related protein (AgRP), pro-opiomelanocortin (POMC), cocaine- and amphetamine-regulated transcript (CART), and melanocortin receptors. Our results indicated that injection time and treatment have a significant effect on food intake. Food intake decreased significantly at 30 and 60 min after ICV administration of DL-Met (1.678 μmol), l-Lys-HCl (6.856 μmol), and Tau (5.006 μmol) compared to the control group (P > 0.05). On the contrary, a high dose of each amino acid did not alter feed intake (P > 0.05). The result showed that ICV injection of DL-Met (1.678 μmol) significantly decreased the mRNA expressions of NPY, NPY4R, and NPY6R (P < 0.05), but had no significant effect on the mRNA expressions of NPY1R, NPY5R, and AgRP in the hypothalamus (P > 0.05). Similarly, ICV injection of l-Lys-HCl (6.856 μmol) and Tau (5.006 μmol) significantly decreased mRNA levels of NPY, NPY4R, and NPY6R (P < 0.05), without affecting the mRNA expressions of NPY1R, NPY5R, and AgRP (P > 0.05). DL-Met had no effect on anorexigenic gene expression (P > 0.05). l-Lys-HCl upregulated MC1R (P < 0.05), and Tau upregulated POMC and MC3R (P < 0.05), and both had no influence on CART, MC4R, or MC5R (P > 0.05). The result suggests that both orexigenic and anorexigenic neuropeptide genes are involved in the effects of DL-Met, l-Lys-HCl, and Tau. The effect of DL-Met, l-Lys-HCl, and Tau acts in a dose-dependent manner in the hypothalamus to influence feed intake.